Markers of Natural Killer Cell Exhaustion in HIV/HCV Coinfection and Their Dynamics After HCV Clearance Mediated by Direct-Acting Antivirals - Osegueda, Ariel (2023)
Background. Liver fibrosis is a leading cause of morbimortality in people with HIV/hepatitis C virus (HCV). Natural killer (NK) cells are linked with amelioration of liver fibrosis; however, NK cells from individuals coinfected with HIV/HCV with cirrhosis display impaired functionality and high PD-1 expression. Here, we aimed to study PD-1, TIGIT, and Tim3 as potential exhaustion markers in NK cells from persons coinfected with HIV/HCV with mild and advanced liver fibrosis. We also evaluated the role of PD-1 expression on NK cells after HCV clearance by direct-acting antivirals (DAAs). Methods. Peripheral blood mononuclear cells were isolated from individuals coinfected with HIV/HCV (N = 54; METAVIR F0/F1, n = 27; F4, evaluated by transient elastography, n = 27). In 26 participants, samples were collected before, at the end of, and 12 months after successful DAA treatment. The frequency, immunophenotype (PD-1, TIGIT, and Tim3 expression), and degranulation capacity (CD107a assay) of NK cells were determined by flow cytometry. Results. Unlike PD-1, Tim3 and TIGIT were comparably expressed between persons with mild and advanced fibrosis. Degranulation capacity was diminished in NK/TIGIT+ cells in both fibrosis stages, while NK/PD-1+ cells showed a lower CD107a expression in cirrhotic cases. Twelve months after DAA treatment, those with advanced fibrosis showed an improved NK cell frequency and reduced NK/PD-1+ cell frequency but no changes in CD107a expression. In individuals with mild fibrosis, neither PD-1 nor NK cell frequency was modified, although the percentage of NK/CD107a+ cells was improved at 12 months posttreatment. Conclusions. Although DAA improved exhaustion and frequency of NK cells in cirrhotic cases, functionality was reverted only in mild liver fibrosis, remarking the importance of an early DAA treatment.